The Postural Effects on Electrical Activities of Heart in Apparently Healthy Young Adults - Chaudhary, S.; Ranamagar, R.; Shrestha, L.; Pun, D. B.; Karmacharya, P.; Mahotra, N. B. (Kathmandu University Medical Journal, 2021)
Background The electrical activities of heart recorded as electrocardiogram (ECG) are mostly done in supine postures. The body postural changes have effects in these electrical activities in heart which needs to be properly recognized. Objective To find the variations in electrocardiogram during postural changes from supine to upright i.e. sitting and standing postures among apparently healthy young adults. Method A cross sectional study was carried out in Manipal College of Medical Sciences after the institutional ethical clearance. The apparently healthy 30 Nepalese male medical students between 18-25 years of age were enrolled. The electrocardiography was elicited in supine, sitting and standing postures in the participants after 5 minutes’ interval between each procedure in each participant. Result The highest mean amplitudes of Q wave were seen in sitting postures (0.12±0.04 mm), R wave in standing postures (1.46±0.55 mm) and S wave also in standing postures (0.23±0.2 mm). The mean amplitudes of Q and S waves showed statistically significant difference when compared between supine and upright postures. The maximum QRS duration was found while sitting (0.08±0.01 ms) and maximum heart rate in standing posture (82.43±10.59/min). The mean comparison of heart rate was statistically highly significant when compared between supine and standing postures. The mean QRS frontal axis was comparatively increased while standing (64.30±39.29). Conclusion The electrical activities of heart vary during postural changes among apparently healthy young adults. These changes are most prominent when compared between supine and standing postures which urges for careful interpretation of electrocardiogram if it is done in upright postures.